Distribution of yttrium 90 ferric hydroxide colloid and gold 198 colloid after injection into knee. - Williams, E D (1976)
Thirteen knees were injected with yttrium 90(90Y) ferric hydroxide colloid, and 12 with gold 198(198Au) colloid for treatment of persistent synovitis. Retention in the knee and uptake in lymph nodes and liver were measured by a quantitative scanning technique. There was no significant difference in the retention in the knee of the two different colloids. A tendency towards higher lymph node uptake was observed with 198Au compared with 90y. The inflammatory activity of the knee at the time of treatment may have influenced the subsequent lymph node uptake of 198Au, but not that of the 90Y, nor the overall leakage of either from the knee. 90Yferric hydroxide colloid was retained in the treated knee at least as well as other colloids which have been used for this purpose.